2020
DOI: 10.3947/ic.2020.52.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Campylobacter Bacteremia as the First Manifestation of Hypogammaglobulinemia: A Case Report and Literature Review

Abstract: A 30-year-old woman with a past medical history of autoimmune hemolytic anemia presented with fever. Blood cultures grew Campylobacter. Her medical history was significant for four prior episodes of Campylobacter gastroenteritis and bacteremia. She received ciprofloxacin for the index presentation, then Meropenem de-escalated to doxycycline 6 months later following recurrence of Campylobacter. This prompted investigation for an immunodeficiency disorder. She was found to have hypogammaglobulinemia. Her Campylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The common underlying conditions in the affected patients included HIV infection, malignancy, liver disease, solid organ transplantation, chronic obstructive pulmonary disease, heart disease and hypogammaglobulinaemia [5]. Studies have also shown that patients having recurrent Campylobacter infections indicates their immunodeficient status and this highlights the importance of suspecting hypogammaglobulinaemia [5, 11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…The common underlying conditions in the affected patients included HIV infection, malignancy, liver disease, solid organ transplantation, chronic obstructive pulmonary disease, heart disease and hypogammaglobulinaemia [5]. Studies have also shown that patients having recurrent Campylobacter infections indicates their immunodeficient status and this highlights the importance of suspecting hypogammaglobulinaemia [5, 11, 12].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, uoroquinolones and macrolides are considered as rst-line agents for the treatment of Campylobacter infections. Nevertheless, high resistance to the above antibacterials were also found in many cases, and might vary in different regions [15]. In addition, clinicians should also take note of the situation that the patients who repeatedly infected with Campylobacter were sensitive to one drug at the beginning, but later developed resistance.…”
Section: Discussionmentioning
confidence: 99%